Liver and Spleen Stiffness Measurements by Point Shear Wave Elastography via Acoustic Radiation Force Impulse: Intraobserver and Interobserver Variability and Predictors of Variability in a US Population. (23rd September 2016) - Balakrishnan, Maya; Souza, Fernanda; Muñoz, Carolina; Augustin, Salvador; Loo, Nicole; Deng, Yanhong; Ciarleglio, Maria; Garcia-Tsao, Guadalupe
Abstract : Objectives: Measurements of liver stiffness and spleen stiffness are useful noninvasive ways to assess fibrosis and portal hypertension in patients with chronic liver disease. One method for assessing stiffness is by point shear wave elastography via acoustic radiation force impulse imaging (ARFI). Its advantage is that sites where stiffness is measured are visualized sonographically. However, its reliability has not been well established, and all studies done to date evaluating the use of ARFI in chronic liver disease have been performed outside the United States. We aimed to characterize the intraobserver and interobserver variability of ARFI‐measured liver and spleen stiffness. Methods: Two hepatologists evaluated unselected hepatology outpatients with ARFI. Exclusions were hepatocellular carcinoma, ascites, a surgical shunt or transjugular intrahepatic portosystemic shunt, portal thrombosis, and cholestatic disease. Each operator obtained 20 measurements from the right liver lobe and spleen. Intraclass correlation coefficients (ICC) were calculated. Results: A total of 177 patients were included: median age, 61 years; 85% male; and 43% obese. Intraobserver ICCs were the same for both observers for liver stiffness (0.89; 95% confidence interval [CI], 0.85–0.92) and spleen stiffness (0.72; 95% CI, 0.61–0.80). Interobserver agreement was excellent for liver stiffness (ICC, 0.85; 95% CI, 0.76–0.90) but not as good for spleen stiffness (ICC, 0.73; 95% CI, 0.60–0.83). A body mass index of 30 kg/m 2 or greater, waist circumference of greater than 105 cm, and skin‐to‐capsule distance of 2 cm or greater negatively affected the ICC for liver stiffness; small spleen size negatively affected the ICC for spleen stiffness. Conclusions: To our knowledge, this article is the first report of ARFI findings in a US population with chronic liver disease. Liver stiffness reproducibility was excellent, particularly in nonobese patients. Spleen stiffness reproducibility was excellent in those with larger spleens and therefore may be most useful in patients with cirrhosis and portal hypertension.